2020
DOI: 10.1186/s12960-020-00490-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to surgery performed by non-physician clinicians in sub-Saharan Africa—a scoping review

Abstract: Background: Sub-Saharan Africa (SSA) faces the highest burden of disease amenable to surgery while having the lowest surgeon to population ratio in the world. Some 25 SSA countries use surgical task-shifting from physicians to non-physician clinicians (NPCs) as a strategy to increase access to surgery. While many studies have investigated barriers to access to surgical services, there is a dearth of studies that examine the barriers to shifting of surgical tasks to, and the delivery of safe essential surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Much of what is known about barriers to scaling-up district level surgery in sub-Saharan Africa is reflected in our findings, such as the importance of infrastructure, motivated staff, adequate supplies and the financial situation of DHs. 19 , 20 When looking specifically at Tanzania, an earlier review by Nyberger et alfound 135 publications about the state of surgery and anesthesia in Tanzania. 4 Like us, they find that major problems were workforce shortages, inefficiencies in the referral system, lack of water/electricity, and inadequate surgical necessities such as equipment and supplies.…”
Section: Discussionmentioning
confidence: 99%
“…Much of what is known about barriers to scaling-up district level surgery in sub-Saharan Africa is reflected in our findings, such as the importance of infrastructure, motivated staff, adequate supplies and the financial situation of DHs. 19 , 20 When looking specifically at Tanzania, an earlier review by Nyberger et alfound 135 publications about the state of surgery and anesthesia in Tanzania. 4 Like us, they find that major problems were workforce shortages, inefficiencies in the referral system, lack of water/electricity, and inadequate surgical necessities such as equipment and supplies.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the absence of a legal framework, lack of official recognition and accreditation, inexact defined responsibilities and poor employment conditions were important demotivating factors for associate clinicians in Sierra Leone, as also described in other sub-Saharan countries. [66][67][68][69] According to a recent review of surgical task-sharing in sub-Saharan Africa, other barriers to surgical tasksharing involved a perceived reduction in surgical skills and outcomes, poor continuous professional development and lack of supervision. 68 Whereas task-sharing has proven its worth in providing safe surgical care in Sierra Leone, and associate clinicians currently perform almost 20% of surgical procedures, 70 71 so far it has not led to the required increase in surgical volume.…”
Section: Barriers To Increasing Surgical Productivitymentioning
confidence: 99%
“…[66][67][68][69] According to a recent review of surgical task-sharing in sub-Saharan Africa, other barriers to surgical tasksharing involved a perceived reduction in surgical skills and outcomes, poor continuous professional development and lack of supervision. 68 Whereas task-sharing has proven its worth in providing safe surgical care in Sierra Leone, and associate clinicians currently perform almost 20% of surgical procedures, 70 71 so far it has not led to the required increase in surgical volume.…”
Section: Barriers To Increasing Surgical Productivitymentioning
confidence: 99%
“…Here, non-specialists are usually the ones performing surgery at the local district hospitals (DHs), as part of DH-level surgical teams that further comprise anesthesia providers, theatre nurses and support staff. 2 Non-specialists face a multitude of barriers to providing surgery, such as shortages of supplies, poor infrastructure, regulatory ambiguities, and lack of training and supervision, 3 which poses challenges to their retention for work in rural areas. 4 In Malawi, a country with 18 million inhabitants of whom 84% live in rural areas, there are only 42 surgical specialists, mostly working in the central hospitals (CHs) of Blantyre and Lilongwe.…”
Section: Introductionmentioning
confidence: 99%